English Reading Performance and Metacognitive Strategies: Implications for Students’ Academic Success - Mercado, Joanna Camille Y.; Manzano, Brendalyn A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Education is not a privilege; it is a human right. In response, Sustainable Development Goals' "Let Me Learn" stated that nearly two-thirds of 10-year-olds can hardly read nor perceive and simplify a text, which is even more severe in the Philippines, where reading is in English. Thus, this research sought to examine the relationship between English reading performance and the metacognitive strategies of the grade 7 students on their word recognition and reading comprehension through the Philippine Informal Reading Inventory to determine their reading profile. In correlation, the Metacognitive Reading Strategies Questionnaire was used to self-assess reading strategies. The quantitative-descriptive correlational research design revealed no significant relationship between English reading performance and metacognitive strategies. However, a significant but weak relationship was seen between oral reading and pragmatic-behavioral strategies. It signifies that they can read some words but can hardly comprehend the reading text. The study's product mainly suggested that the variables do not correlate, concluding that to move toward equitable educational outcomes for an increase in their reading level, reimagining how to foster and reinforce the students to discover and strengthen their gradual progress in reading must at least be achieved to meet the expectations and specifications throughout the act of reading.